2012
DOI: 10.4028/www.scientific.net/msf.730-732.703
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Physical Properties of Multicomponent Alloy on the Simulation Solidification by Phase-Field Model

Abstract: A phase-field model is proposed for the simulation of microstructure and solute concentration during the solidification of Fe-C-P-Mn quaternary alloys. In this paper, a study is presented to analyze both the effects of partition coefficient and solute diffusivity on the microstructural evolution during solidification simulation. Partition coefficient and diffusivity are very important from a practical standpoint, because both parameters exert a strong influence on the dendrite morphology. Additionally, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The solidification thermal parameters have influence on the microstructure and microsegregation andthese, in turn, are key featuresin inducing non-uniformity on the as-cast material mechanical properties. For this reason, the microstructure and microsegregation has been extensively studied both theoretically [1][2][3][4][5][6][7][8][9][10][11] and experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25] for the last decades. The Al-1.2wt%Pb and Al-3.2wt%Bi alloys have been chosen by Freitas et al 13 , to study the effect of microstructural parameters on the wear process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solidification thermal parameters have influence on the microstructure and microsegregation andthese, in turn, are key featuresin inducing non-uniformity on the as-cast material mechanical properties. For this reason, the microstructure and microsegregation has been extensively studied both theoretically [1][2][3][4][5][6][7][8][9][10][11] and experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25] for the last decades. The Al-1.2wt%Pb and Al-3.2wt%Bi alloys have been chosen by Freitas et al 13 , to study the effect of microstructural parameters on the wear process.…”
Section: Introductionmentioning
confidence: 99%
“…where C S is the concentration in the solid region, C 0 the initial overall composition and F S the solid fraction. Although the influence of solidification speed (V L ) and cooling rate ( ) on the microstructural characteristics was the focus of many studies [1][2][3][4][12][13][14][15][16] , literature on the influence of these parameters on the microsegregation profiles are still quite limited 21 . Burton et al 9 proposed an equation for effective distribution coefficient (K ef ) as a function of the solidification speed (V L ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solidification process of alloys has been studied by Salvino et al 1,2 It is shown, in said work, the phase-field model applied to the multicomponent alloy solidification (Fe-C-P-Mn) for equiaxed dendritic growth. The papers provide an introduction to the phase-field model and an overview of its possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of cooling rate on the secondary dendrite arm spacing and microsegregation was investigated through comparison with the experimental results. The previous works [1][2][3][4][5][6] indicate that the phase-field model is a versatile and powerful technique for calculating the evolution of microstructure, which is very popular nowadays.…”
Section: Introductionmentioning
confidence: 99%